2015
DOI: 10.1002/sdtp.10462
|View full text |Cite
|
Sign up to set email alerts
|

20.2: Ultra‐Bright, Highly Efficient, Low Roll‐Off Inverted Quantum‐Dot Light Emitting Devices (QLEDs)

Abstract: We report an ultra-bright, highly efficient, low roll-off, inverted quantum dot-based red light emitting device (QLED) using solution-processed zinc oxide nanoparticles and cesium carbonate films as the electron injection and hole blocking layers, respectively. Record luminance of 165,000 Cd/m 2 has been obtained at a current density of 1000 mA/cm 2 with a low driving voltage of 5.8 V for deep red device with CIE coordinates of (0.69, 0.31).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…In particular, our group has reported ultrabright and efficient deep red QLEDs. 7 As shown in Fig. 1, the devices demonstrate peak emission wavelength of 620 nm, narrow bandwidth of 22 nm and can achieve high current efficiency (20.5 Cd/A at~20 000 Cd/m 2 ) and small efficiency roll-off at high driving current density.…”
Section: Background For Quantum Dot Light Emitting Devices and Photommentioning
confidence: 90%
See 2 more Smart Citations
“…In particular, our group has reported ultrabright and efficient deep red QLEDs. 7 As shown in Fig. 1, the devices demonstrate peak emission wavelength of 620 nm, narrow bandwidth of 22 nm and can achieve high current efficiency (20.5 Cd/A at~20 000 Cd/m 2 ) and small efficiency roll-off at high driving current density.…”
Section: Background For Quantum Dot Light Emitting Devices and Photommentioning
confidence: 90%
“…Among QLEDs of various colors, red QLEDs are currently most advanced and have demonstrated efficiency and brightness that rival or beat state‐of‐the‐art thermal‐evaporated red OLEDs, with narrow peak linewidths in the 20 to 30‐nm range. In particular, our group has reported ultrabright and efficient deep red QLEDs . As shown in Fig.…”
Section: Background For Quantum Dot Light Emitting Devices and Photommentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the efficiency roll-off was significantly eliminated and the EQE reached 20%, which is the theoretical maximum for planar devices without extraction features. To address the efficiency roll-off issue, Dong et al recently proposed the use of a Cs 2 CO 3 layer for hole-blocking together with an electron injecting a ZnO nanoparticle layer [75]. This redemitting device surpassed the brightness of organic LEDs at a value of 165,000 cd/m 2 at 1000 mA/cm 2 current density.…”
Section: Electroluminescent Devices Of Colloidal Materials For Lightingmentioning
confidence: 99%
“…Although the majority of the aforementioned studies to improve charge balance have shown notable achievements in the device performances, sophisticated efforts such as researching an efficient interfacial treatment to block excess electrons without chemically harming the bottom layer or precisely controlling the inserted insulating layer thickness are indispensable . Thus, we focus on a simple and low‐cost method using a metal‐doped ZnO ETL to suppress excess electron injection and improve the device performance.…”
Section: Introductionmentioning
confidence: 99%